Creating integral value for stakeholders in closed loop supply chains. Issue 3 (September 2015) - Schenkel, Maren; Krikke, Harold; Caniëls, Marjolein C.J.; der Laan, Erwin van
Abstract This paper contributes to the existing literature by researching integral value creation in closed loop supply chains (CLSCs). We distinguish between multiple types of business value, strategic success factors, and multiple groups of stakeholders that affect and are affected by CLSC activities. To gain empirical evidence, we collect and analyze in-depth data of four case studies in business to business markets in high capital goods. Our findings show that CLSC activities create opportunities and reduce risks for the focal company and their primary and secondary stakeholders. Strategic success factors such as product design, customer services, and CLSC business models modify CLSC processes and, hence, increase value. Intra-and inter organizational information sharing and stakeholder relationships strengthen value creation by influencing the strategic success factors. We conclude with the formulation of propositions.